Starting out with Java early objects - Gaddis, Tony (Pearson, 2015)
In Starting Out with Java: Early Objects, Gaddis looks at objects-the fundamentals of classes and methods-before covering procedural programming. As with all Gaddis texts, clear and easy-to-read code listings, concise and practical real-world examples, and an abundance of exercises appear in every chapter.